The Effect Of Competence, Morality, Integrity, Internal Control, And Organizational Culture On Fraud Prevention With Whistleblowing System As Moderating Variables - Meita Risma Cahyani; Ida Ayu Putu Meita Puspa Aristanti; Anak Agung Putu Gede Bagus Arie Susandya; M Doni Permana Putra; I Kadek Bagiana (Jurnal Mantik, 2022)
This study aims to determine the effect of apparatus competence, apparatus morality, apparatus integrity, internal control and organizational culture on the prevention of fraud that occurs in the management of village fund allocations with the whistleblowing system as a moderating variable in the Village Office in Baturiti sub-district. This study uses a quantitative descriptive design. The population in this study were village officials in Baturiti sub-district totaling 84 people. The sample uses a saturated sample. Data obtained from the distribution of questionnaires to respondents who have been determined. The data analysis technique used the MRA test. The results showed that the morality of the apparatus, the integrity of the apparatus and the organizational culture had no influence on the prevention of fraud in the management of village fund allocations. The internal control variable has a positive and significant effect on preventing fraud in managing village fund allocations, while the competence of the apparatus has a negative effect on preventing fraud in managing village fund allocations. And the whistleblowing system has been proven to moderate the influence of competence, internal control and organizational culture on fraud prevention in the management of village fund allocations, while the whistleblowing system does not moderate the morality of the apparatus and the integrity of the apparatus towards preventing fraud in the management of village fund allocations. The internal control variable has a positive and significant effect on preventing fraud in managing village fund allocations, while the competence of the apparatus has a negative effect on preventing fraud in managing village fund allocations. And the whistleblowing system has been proven to moderate the influence of competence, internal control and organizational culture on fraud prevention in the management of village fund allocations, while the whistleblowing system does not moderate the morality of the apparatus and the integrity of the apparatus towards preventing fraud in the management of village fund allocations. The internal control variable has a positive and significant effect on preventing fraud in managing village fund allocations, while the competence of the apparatus has a negative effect on preventing fraud in managing village fund allocations. And the whistleblowing system has been proven to moderate the influence of competence, internal control and organizational culture on fraud prevention in the management of village fund allocations, while the whistleblowing system does not moderate the morality of the apparatus and the integrity of the apparatus towards preventing fraud in the management of village fund allocations.